Analysis of Very High Frequency Extended Range 134.1 MHz Signal Interference at AirNav Surabaya Branch - Elizabeth Rindi Novitri; Feti Fatonah; Toni (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
In aviation navigation systems, radio communication between pilots and air traffic controllers (ATC) plays a crucial role in ensuring flight safety and efficiency. A disruption known as a blank spot occurred in the Very High Frequency Extended Range (VHF-ER) system on frequency 134.1 MHz in the Upper Pangkalan Bun (UPKN) sector managed by AirNav Indonesia, Surabaya Branch. This interference caused signal loss between pilots and ATC, leading to potential air traffic miscoordination. This study aims to analyze the root causes of the signal disruption and propose technical solutions to improve communication reliability. A qualitative descriptive method was applied, using a fishbone diagram to identify contributing factors from five aspects: human, machine, method, material, and environment. The results indicate a positive correlation between equipment management quality and VHF-ER communication reliability. Key contributing factors include limited technician numbers, lack of training, the use of sectoral antennas with narrow coverage, and improper antenna placement that does not meet technical standards. The implemented solution was replacing sectoral antennas with omnidirectional types. Regular performance checks and strict SOP implementation also helped enhance communication quality. The study recommends improving technician competency, reassessing antenna placement, and conducting routine maintenance as preventive actions.